1981
DOI: 10.1037/0022-0167.28.4.309
|View full text |Cite
|
Sign up to set email alerts
|

Attractive versus unattractive clients: Mediating influences on counselor's perceptions.

Abstract: This study investigated the effects of clients' age, physical attractiveness, and in-session behavior on subjects' attraction to the clients. Female undergraduates were assigned to one of eight experimental conditions in which the client was depicted as (a) an adult or a child, (b) physically attractive or unattractive, and (c) verbal ("good" in-session behavior) or nonverbal ("bad" in-session behavior). The results indicated that "counselor" subjects were significantly more attracted to child than to adult cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Internal consistency reliabilities greater than .80 have been reported for scores on the scale (Tryon, 1989). Counselors' TPRQ scores have been found to be highest for clients rated high on conceptual level (Davis et al, 1977) and verbal ability (Lewis, Davis, Walker, & Jennings, 1981). We slightly altered some items to reflect that participants had not actually worked with the fictional client.…”
Section: Methodsmentioning
confidence: 99%
“…Internal consistency reliabilities greater than .80 have been reported for scores on the scale (Tryon, 1989). Counselors' TPRQ scores have been found to be highest for clients rated high on conceptual level (Davis et al, 1977) and verbal ability (Lewis, Davis, Walker, & Jennings, 1981). We slightly altered some items to reflect that participants had not actually worked with the fictional client.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, the estimated internal consistency reliability was .75. Counselors' TPRQ scores have been found to be highest for clients rated high on conceptual level (Davis et al, 1977) and verbal ability (Lewis, Davis, Walker, & Jennings, 1981).…”
Section: Instrumentsmentioning
confidence: 99%
“…Client motivation is only one of the client variables that has been addressed by counseling researchers. Other authors have found that client characteristics such as: similarity of counselor-client conceptual level (Davis, Cook, Jennings, & Heck, 1977), client, need (Heppner & Dixon, 1978) and client commitment to change (Dixon & Claiborn, 1981), client expectations (Friedlander, 1982;Sobel & O'Brien, 1979), and the perceived attractiveness of the client (Lewis, Davis, Walker, & Jennings, 1981) have been worthy of consideration. In addition, some researchers have found that client characteristics such as resistance and opposition (Kerr, Olson, Claiborn, Gruenler, & Paolo, 1983) and a subscription to myths about career development (Dorn, in press-a) mediate the counselor's social power.…”
Section: Influence As a Two-way Exchangementioning
confidence: 99%